A Small Molecule Inhibitor of PDK1/PLCy1 Interaction Blocks Breast and Melanoma Cancer Cell Invasion. - Raimondi, C.; Calleja, V.; Ferro, R.; Fantin, A.; Riley, A.; Potter, B.; Brennan, C.; Maffucci, T.; Larijani, B.; Falasca, Marco (Nature Publishing Group, 2016)
Strong evidence suggests that phospholipase Cγ1 (PLCγ1) is a suitable target to counteract tumourigenesis and metastasis dissemination. We recently identified a novel signalling pathway required for PLCγ1 activation which involves formation of a protein complex with 3-phosphoinositidedependent protein kinase 1 (PDK1). In an effort to define novel strategies to inhibit PLCγ1-dependent signals we tested here whether a newly identified and highly specific PDK1 inhibitor, 2-O-benzyl-myoinositol 1,3,4,5,6-pentakisphosphate (2-O-Bn-InsP5), could affect PDK1/PLCγ1 interaction and impair PLCγ1-dependent cellular functions in cancer cells. Here, we demonstrate that 2-O-Bn-InsP5 interacts specifically with the pleckstrin homology domain of PDK1 and impairs formation of a PDK1/PLCγ1 complex. 2-O-Bn-InsP5 is able to inhibit the epidermal growth factor-induced PLCγ1 phosphorylation and activity, ultimately resulting in impaired cancer cell migration and invasion. Importantly, we report that 2-O-Bn-InsP5 inhibits cancer cell dissemination in zebrafish xenotransplants. This work demonstrates that the PDK1/PLCγ1 complex is a potential therapeutic target to prevent metastasis and it identifies 2-O-Bn-InsP5 as a leading compound for development of anti-metastatic drugs.